Sindrom visceralne gojaznosti i kardiometabolizam - Ferreira Lopes, Heno; Egan, Brent M (Scripta Medica, 2021)
The distribution of fat in the human body is related to hemodynamic and metabolic homeostasis. Brown fat is inversely related to body mass index and is associated with a lower probability of developing diabetes. Beige adipose tissue shares some functional characteristics with brown adipose tissue. White adipose tissue constitutes the majority of the fatty tissue and is mainly distributed in the subcutaneous and abdominal cavity. Intra-abdominal white fat has gained prominence in recent years for its association with cardiovascular risk factors and higher cardiovascular mortality. This review article discusses the human adaptation in the environment, a sympathovagal and hypothalamic-pituitary-adrenal imbalance as a possible cause of increased visceral adiposity and its consequences on cardiometabolism.
Keywords: Visceralna gojaznost; Simpatički nervni sistem; Hipotalamusno-hipofizno-nadbubrežna osovina; Kardiometabolizam